2013
DOI: 10.1517/14712598.2014.858116
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of erythropoiesis-stimulating agent use in the perioperative period

Abstract: Current evidence supports the use of perioperative ESAs to reduce the need for ABT. However, large studies assessing safety in anemic patients with chronic renal disease have found adverse effects including cardiovascular, stroke and thromboembolic events. However, whether these concerns can be conferred onto the surgical population remains to be seen as the perioperative dosing strategies have been more variable in timing, dose and duration in comparison with those used for chronic diseases. Future research n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
1
12
0
1
Order By: Relevance
“…10,26 Studies have reported EBL as high as 60%-100% of estimated blood volume (EBV) with almost all patients undergoing a blood transfusion during or immediately after the surgery. 16,32,34 Our results were consistent with the high EBL presented in previous studies, with a 15 ml/kg average EBL (18% EBV) for the C group and 23.5 ml/kg (29% EBV) for the protocol group. Techniques for surgical repair of craniosynostosis have the goal of achieving a long-term normocephaly while minimizing risk, including the need for transfusion.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…10,26 Studies have reported EBL as high as 60%-100% of estimated blood volume (EBV) with almost all patients undergoing a blood transfusion during or immediately after the surgery. 16,32,34 Our results were consistent with the high EBL presented in previous studies, with a 15 ml/kg average EBL (18% EBV) for the C group and 23.5 ml/kg (29% EBV) for the protocol group. Techniques for surgical repair of craniosynostosis have the goal of achieving a long-term normocephaly while minimizing risk, including the need for transfusion.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the low incidence of such events in these studies, no clear correlation with EPO treatment could be made. 13,25,27,32 A concern for EPO use is the development of thrombotic complications associated with the higher hematocrit resulting from EPO therapy. The occurrence of thrombotic events in children receiving EPO is very low (0.07-0.14 per 10,000 children in the general population).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important point of distinction is that many studies reporting on the thromboembolic risks of ESAs are from patients with chronic renal disease, who are typically treated with higher doses over longer time, and high-risk populations such as critically ill and cancer patients [33,34], as opposed to the use of ESA in the preoperative setting, which typically involves much lower duration of treatment and lower doses often used in combination with anticoagulants [35]. Some evidence suggests treatment with ESAs to achieve arbitrary haemoglobin levels as treatment targets may result in some patients (those with ESA resistance) receiving exceedingly large doses of ESA, which may expose them to higher risk of complications [4 && ,36].…”
Section: Role Of Intravenous Iron and Erythropoiesis-stimulating Agentsmentioning
confidence: 99%